FAKTOR-FAKTOR YANG MEMPENGARUHI INITIAL RETURN PERUSAHAAN DI INDONESIA - Mahirun; Khoiri Yanti; Titi Rahayu Prasetiani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Abstract. This study aimed to analyze the effect of debt to equity ratio, return on equity ratio, underwriter reputation, percentage of stock offerings, firm size, and earnings per share on initial return. The population of this research is 201 companies do in an Initial Public Offering (IPO) listed on the Indonesia Stock Exchange in 2017 to 2020. The total sample of this research are 133 companies which have the requirements. The analyze data in this study using the multiple linear regression models and there are 91 companies for classic assumption test. The results of this study showed, the debt to equity ratio and return on equity have a negative effect, but not significant on the initial return. The underwriter's reputation become the concentration of investors. Shares offered and firm size give the great affect for investors make a decision. From this study, the conclution is the biggest reason investors buy shares offered is the amount of earnings per share Keywords: initial return; underwriter; return on equity; earning per share; debt to equity ratio; firm size; universitas pekalongan